Preparation method of polyacid-hydrogel-based self-supporting electrocatalyst

By modifying the borax-crosslinked molybdenum-based PVA-CS hydrogel on the carbon paper matrix, aerogel with a 3D porous mesh structure was formed, and high-temperature carbonization and electrodeposition were performed to prepare polyacid-water with low Pt loading. Gel-based self-supported electrocatalyst solves the problems of high cost and poor mechanical properties of precious metal catalysts, and achieves efficient and stable electrocatalytic performance.

CN119433612APending Publication Date: 2025-02-14QINGDAO BINHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895063.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the high cost and low reserves of precious metal catalysts limit the sustainable clean production of hydrogen energy, and the mechanical properties of polymer aerogel materials after high-temperature carbonization are poor, affecting the electrocatalytic performance.

Method used

By modifying the borax-crosslinked molybdenum-based PVA-CS hydrogel on a carbon paper matrix, a 3D porous mesh-like aerogel was formed after freeze-drying, followed by high-temperature carbonization and electrodeposition to prepare a low Pt load Polyacid-hydrogel-based self-supporting electrocatalyst.

Benefits of technology

A low Pt content and efficient electrocatalyst preparation is achieved, reducing the amount of precious metals, improving catalytic activity and stability, and promoting electron transfer and mass transfer through 3D porous structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433612A_ABST
    Figure CN119433612A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electric water desorption hydrogen desorption catalysis, and relates to a preparation method of a polyacid-hydrogel-based self-supporting electrocatalyst, which comprises the following steps: uniformly mixing a chitosan solution and a polyvinyl alcohol solution in proportion to obtain a PVA-CS solution; soaking hydrophilic carbon paper in the PVA-CS solution, and placing the hydrophilic carbon paper in a borax solution after the hydrophilic carbon paper is soaked uniformly; putting the PVA-CS-polyacid aerogel into a molybdate solution, standing for 11-13 hours at-25 DEG C to-15 DEG C, and freeze-drying to obtain PVA-CS-polyacid aerogel modified carbon paper; the preparation method comprises the following steps: preparing a polyacid-hydrogel-based self-supporting electrocatalyst, placing the polyacid-hydrogel-based self-supporting electrocatalyst in an N2 atmosphere, carbonizing at 700-900 DEG C for 2-4 hours, and placing the carbonized material in an electrolyte containing chloroplatinic acid for electrodeposition to obtain the polyacid-hydrogel-based self-supporting electrocatalyst. The low-Pt-content electrocatalyst with excellent HER performance is prepared through a simple method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic water decomposition hydrogen catalysis, and specifically relates to a method for preparing a polyacid-hydrogel-based self-supporting electrocatalyst. Background Art

[0002] Hydrogen energy is a recognized clean energy with the characteristics of zero pollution and high energy. It is an ideal green energy. The development of new hydrogen energy in China is in a period of rapid growth. The hydrogen energy industry has become an important direction for China's energy structure transformation. Policy support, technological innovation progress and huge market potential have provided strong support for the development of the hydrogen energy industry. Hydrogen production by water electrolysis is one of the most promising methods for obtaining green hydrogen energy. Hydrogen production by water electrolysis includes hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anode. Water electrolysis is an efficient and green hydrogen production method, which can be theoretically divided into two separate half reactions: hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anode. However, the kinetics of these two reactions are very slow and usually require overcoming large overpotentials to proceed. So far, precious metal catalysts such as Pt, Ru and Ir are often used for efficient HER and OER. Among them, precious metal platinum (Pt) catalysts are widely used in HER reactions due to their excellent catalytic performance. They are considered to be the most efficient and stable commercial HER electrocatalysts and have been widely used in hydrogen production and fuel cells. Pt exhibits excellent catalytic activity under acidic and neutral conditions, but the high price and extremely low reserves of precious metals such as platinum have largely limited the large-scale commercialization of water electrolysis hydrogen production technology. Therefore, the development of low-cost, efficient and stable electrocatalysts is of great research significance for the sustainable and clean production of hydrogen energy.

[0003] Hydrogel is a kind of elastomeric material containing water and polymers. Its composition structure is adjustable, easy to prepare and functionalize. By flexibly introducing active functional groups with positive charges, it can adsorb polyacid anion clusters. Hydrogel materials have excellent pore structure and surface modifiability, and are considered to be an ideal platform for synthesizing high-performance electrocatalytic materials. Hydrogels can be used to prepare aerogels after freeze-drying. Its multi-level pore structure can improve the mass transfer rate, the continuous conductive network skeleton can accelerate the charge transfer, and the high internal specific surface area can provide abundant active sites, further improving the catalytic effect. However, polymer aerogels after high-temperature carbonization are usually brittle and have poor mechanical properties. This makes it necessary to add a binder to attach it to a conductive substrate during the preparation of electrode materials. The presence of the binder will hinder the conduction of electrons to a certain extent, increase the resistance of the electrode, and is not conducive to the rapid transfer of electrons in the electrocatalytic reaction, thereby affecting the electrocatalytic performance. In addition, the binding force between the powder particles is weak. During long-term use, the catalyst is easy to fall off, shift or re-agglomerate, resulting in changes in the electrode structure and performance, affecting its service life.

[0004] In order to solve the above problems, the present invention designs and develops a new preparation method for preparing a polyacid-hydrogel-based self-supporting electrocatalyst with low cost and good catalytic activity. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art, and a method for preparing a polyacid-hydrogel-based self-supporting electrocatalyst is proposed. A low Pt loading electrocatalyst with excellent hydrogen evolution reaction (HER) performance is prepared by electrodeposition of Pt on a hydrogel-derived aerogel-modified carbon paper substrate.

[0006] The technical solution of the present invention is:

[0007] The present invention provides a method for preparing a polyacid-hydrogel-based self-supporting electrocatalyst, comprising the following steps:

[0008] (1) mixing the prepared CS solution and the PVA solution in a chitosan (CS) to polyvinyl alcohol (PVA) mass ratio of 1:(3-5), stirring until uniform, and obtaining a PVA-CS solution;

[0009] (2) soaking the hydrophilic carbon paper in a PVA-CS solution, then placing it in a borax solution for a period of time to obtain a cross-linked PVA-CS hydrogel-modified carbon paper, then placing it in a molybdate solution for 3 to 7 minutes, then placing it at a temperature of -25 to -15°C for 11 to 13 hours, and then freeze-drying it to obtain a PVA-CS-polyacid aerogel-modified carbon paper;

[0010] (3) The PVA-CS-polyacid aerogel-modified carbon paper was placed in a N2 atmosphere and carbonized at 700-900°C for 2-4 h. The carbonized material was then placed in a solution containing chloroplatinic acid for electrodeposition to obtain a polyacid-hydrogel-based self-supporting electrocatalyst (Pt@MoCx / CFP electrocatalyst).

[0011] The heating rate of the step (3) to the carbonization temperature of 700-900°C is 5°C / min.

[0012] Furthermore, in the step (1), a certain mass of CS is weighed and dissolved in a 1% glacial acetic acid solution, and stirred until dissolved to obtain a 2.5% CS solution; a certain mass of PVA is weighed and added to deionized water, and stirred at 80-95° C. for 1.5-2.5 hours to obtain a 10% PVA solution; the 2.5% CS solution and the 10% PVA solution are mixed at a CS:PVA mass ratio of 1:4, and stirred until uniform to obtain a PVA-CS solution.

[0013] Furthermore, in step (2), the hydrophilic carbon paper is cut into 1×1.5 cm, immersed in the PVA-CS solution, and then scraped on both sides after immersion, and then placed in a 4% concentration borax solution for 30 seconds;

[0014] The hydrophilic carbon paper may also be replaced by hydrophilic carbon cloth.

[0015] Furthermore, the ratio of the mass of the molybdate used in the step (2) to the mass of CS is (2-4):1, and the molybdate solution includes ammonium molybdate tetrahydrate.

[0016] Furthermore, in step (3), the solution containing chloroplatinic acid is a mixed solution of chloroplatinic acid solution and sodium hydroxide solution; in the solution containing chloroplatinic acid, the concentration of chloroplatinic acid is 20 μmol / L to 100 μmol / L.

[0017] Furthermore, in step (3), the carbonized material is used as the working electrode, graphite is used as the counter electrode, and saturated calomel is used as the reference electrode, and electrodeposition is performed in a solution containing chloroplatinic acid. The deposition conditions are: in CV mode, the scan rate is 50 mV s -1 The deposition voltage range is 0 to -0.50 V versus RHE, the cycle is 100 to 1000 cycles, and the optimal condition is 400 cycles.

[0018] The present invention also provides a polyacid-hydrogel-based self-supporting electrocatalyst obtained by any of the above-mentioned preparation methods.

[0019] The present invention also provides the use of the polyacid-hydrogel-based self-supporting electrocatalyst in hydrogen production by electrolysis of water.

[0020] Beneficial effects of the present invention:

[0021] (1) The present invention prepares a low Pt content and high efficiency electrocatalyst, which is prepared by modifying a borax-crosslinked molybdenum-based PVA-CS hydrogel on a carbon paper substrate, and obtaining an aerogel with a 3D porous network structure after freeze-drying, and then obtaining an integrated self-supporting electrocatalyst after high-temperature carbonization and electrodeposition;

[0022] The integrated self-supporting electrocatalyst (Pt@MoCx / CFP electrocatalyst) prepared by the present invention has only 0.54wt% Pt loading, and the amount of Pt precious metal used is relatively small, which reduces the cost while improving the catalytic activity and stability of the electrocatalyst; in addition, the design of the 3D porous network structure provides a channel for rapid electron transfer and effective mass transfer.

[0023] (2) The introduction of Mo element into Pt-based electrocatalysts can significantly reduce the energy barrier of water dissociation and H2 adsorption energy, thereby reducing the overpotential during the hydrogen evolution reaction.

[0024] (3) The present invention combines the positively charged chitosan with the negatively charged polyacid solution through electrostatic interaction, and then disperses Pt through the polyacid, so that the Pt element can be evenly dispersed on the Mo-based 3D conductive porous aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD patterns of different catalysts;

[0026] Figure 2 To show the LSV curves of different catalysts;

[0027] Figure 3 The current density is 10 mA / cm 2 and 100mA / cm 2 The hydrogen evolution overpotential;

[0028] Figure 4 is the Tafel slope obtained by LSV curve fitting for different electrocatalysts;

[0029] Figure 5 Impedance spectra of different electrocatalysts in 1 mol / L KOH solution. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In order to further understand the present invention, the present invention will be further described in conjunction with the accompanying drawings and embodiments.

[0032] Example 1

[0033] (1) Weigh 1.25 g of chitosan (CS) and dissolve it in 50 mL of 1% glacial acetic acid solution, stir for 1 h until dissolved, to obtain a 2.5% CS solution, cover with plastic wrap, and set aside; weigh 1 g of polyvinyl alcohol (PVA) and place it in 9 g of deionized water, stir at 90°C for 2 h, to obtain a 10% PVA solution, cover with plastic wrap, and set aside; respectively measure 4 mL of 10% PVA solution and 4 mL of 2.5% CS solution, mix, and stir for 5 min until uniform, to obtain a PVA-CS solution;

[0034] (2) Cut the hydrophilic carbon paper into 1×1.5 cm, soak it in the above PVA-CS solution, and scrape it on both sides after soaking; then place it in a 4% concentration borax solution for 30 seconds; then place it in ammonium molybdate tetrahydrate (NH4)6Mo7O 24 ·4H2O) for 5 min, then placed in a refrigerator at -20 degrees Celsius for 12 hours, and then transferred to a cold dryer for freeze drying for 12 hours to obtain PVA-CS-polyacid aerogel-modified carbon paper;

[0035] (3) The carbon paper modified with PVA-CS-polyacid aerogel was placed in a tube furnace and carbonized at 800°C for 3 h in a N2 atmosphere to obtain a carbonized material; the carbonized material was placed in a solution containing chloroplatinic acid for electrodeposition. (The electrodeposition steps are as follows: the carbonized material is used as the working electrode, graphite is used as the counter electrode, and saturated calomel is used as the reference electrode. 60 mL of 60 μmol / L chloroplatinic acid solution is taken for electrodeposition; in the CV mode, the scan rate is 50 mV s -1 , and the deposition voltage was cycled for 400 cycles under the condition of 0 to -0.50 V versus RHE).

[0036] Example 2

[0037] (1) Weigh 1.25 g of chitosan (CS) and dissolve it in 50 mL of 1% glacial acetic acid solution, stir for 1 h until dissolved, to obtain a 2.5% CS solution, cover with plastic wrap, and set aside; weigh 1 g of polyvinyl alcohol (PVA) and place it in 9 g of deionized water, stir at 95°C for 1.5 h, to obtain a 10% PVA solution, cover with plastic wrap, and set aside; respectively measure 3 mL of 10% PVA solution and 4 mL of 2.5% CS solution, mix, and stir for 5 min until uniform, to obtain a PVA-CS solution;

[0038] (2) Cut the hydrophilic carbon paper into 1×1.5 cm, soak it in the above PVA-CS solution, and scrape it on both sides after soaking; then place it in a 4% concentration borax solution for 30 seconds; then place it in ammonium molybdate tetrahydrate (NH4)6Mo7O 24 ·4H2O) for 3 min, then placed in a refrigerator at -20 degrees Celsius for 13 hours, and then transferred to a cold dryer for freeze drying for 12 hours to obtain PVA-CS-polyacid aerogel-modified carbon paper;

[0039] (3) The carbon paper modified with PVA-CS-polyacid aerogel was placed in a tube furnace and carbonized at 700°C for 3 h in a N2 atmosphere to obtain a carbonized material; the carbonized material was placed in a solution containing chloroplatinic acid for electrodeposition. (The electrodeposition steps are as follows: the carbonized material is used as the working electrode, graphite is used as the counter electrode, and saturated calomel is used as the reference electrode. 60 mL of 20 μmol / L chloroplatinic acid solution is taken for electrodeposition; in the CV mode, the scan rate is 50 mV s-1 , and the deposition voltage was cycled for 100 cycles under the condition of 0 to -0.50 V versus RHE).

[0040] Example 3

[0041] (1) Weigh 1.25 g of chitosan (CS) and dissolve it in 50 mL of 1% glacial acetic acid solution, stir for 1 h until dissolved to obtain a 2.5% CS solution, cover with plastic wrap and set aside; weigh 1 g of polyvinyl alcohol (PVA) and place it in 9 g of deionized water, stir at 80°C for 2.5 h to obtain a 10% PVA solution, cover with plastic wrap and set aside; respectively measure 5 mL of 10% PVA solution and 4 mL of 2.5% CS solution, mix, and stir for 5 min until uniform to obtain a PVA-CS solution;

[0042] (2) Cut the hydrophilic carbon paper into 1×1.5 cm, soak it in the above PVA-CS solution, and scrape it on both sides after soaking; then place it in a 4% concentration borax solution for 30 seconds; then place it in ammonium molybdate tetrahydrate (NH4)6Mo7O 24 ·4H2O) for 7 min, then placed in a refrigerator at -20 degrees Celsius for 11 hours, and then transferred to a cold dryer for freeze drying for 12 hours to obtain PVA-CS-polyacid aerogel-modified carbon paper;

[0043] (3) The carbon paper modified with PVA-CS-polyacid aerogel was placed in a tube furnace and carbonized at 900°C for 3 h in a N2 atmosphere to obtain a carbonized material; the carbonized material was placed in a solution containing chloroplatinic acid for electrodeposition. (The electrodeposition steps are as follows: the carbonized material is used as the working electrode, graphite is used as the counter electrode, and saturated calomel is used as the reference electrode. 60 mL of 100 μmol / L chloroplatinic acid solution is taken for electrodeposition; in the CV mode, the scan rate is 50 mV s -1 , and the deposition voltage was cycled for 1000 times under the condition of 0~-0.50Vversus RHE).

[0044] Test Example 1

[0045] The Pt@MoCx / CFP prepared in Example 1 of the present invention, Figure 1 Figure 2 is the XRD spectrum of different electrocatalysts, from which the peaks of Pt and C can be observed.

[0046] Test Example 2

[0047] The performance of the Pt@MoCx / CFP, Pt / CFP, MoCx / CFP and Pt / C catalysts prepared in Example 1 of the present invention was tested.

[0048] The difference between the preparation of Pt / CFP and Example 1 is that ammonium molybdate tetrahydrate is not added, and the other steps are the same as those in Example 1. The difference between the preparation of MoCx / CFP and Example 1 is that Pt is not electrodeposited, and the other steps are the same as those in Example 1.

[0049] The preparation steps of Pt / C include: (1) Catalyst preparation: take 5 mg of 20% platinum carbon catalyst and grind it thoroughly into a 2 ml centrifuge tube, then use a pipette to take 100 μl of Nafion and 900 μl of isopropanol into a 2 ml centrifuge tube, and use ultrasonic cleaning for 30 minutes to make it completely uniform; (2) Drop coating: take 100 μl of solution and drop it onto a 1 cm 2 On the titanium mesh, dry it.

[0050] The performance test results are as follows:

[0051] Figure 2 The LSV curves of different catalysts are shown, indicating that Pt@MoCx / CFP has the highest HER performance among the catalysts.

[0052] Figure 3 The Pt@MoCx / CFP electrocatalyst has a high conductivity at 10 and 100 mA / cm 2 At current densities of only 13 mV and 135 mV are required, respectively, which are lower than Pt / CFP (33, 224 mV), MoCx / CFP (178, 349 mV) and Pt / C catalysts (21, 166 mV).

[0053] Figure 4 is the Tafel slope obtained by LSV curve fitting for different electrocatalysts, among which the Tafel slope of Pt@MoCx / CFP catalyst (69.29 mV / dec) is smaller than that of Pt / CFP (72.66 mV / dec) and MoCx / CFP (217.13 mV / dec) electrocatalysts, which means that the electrochemical reaction kinetics is faster.

[0054] Figure 5 The impedance spectra of different electrocatalysts in 1 mol / L KOH solution. The Pt@MoCx / CFP catalyst has a lower resistance value of 2.64 ohm, which indicates that the Pt@MoCx / CFP catalyst has efficient charge transfer ability in the hydrogen evolution reaction.

[0055] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacid-hydrogel-based self-supporting electrocatalyst, characterized in that: The following steps are involved: (1) mixing the prepared chitosan solution and the polyvinyl alcohol solution in a chitosan to polyvinyl alcohol mass ratio of 1:(3-5), stirring until uniform, to obtain a PVA-CS solution; (2) soaking the hydrophilic carbon paper in a PVA-CS solution, then placing it in a borax solution for a period of time to obtain a cross-linked PVA-CS hydrogel-modified carbon paper, then placing it in a molybdate solution for 3 to 7 minutes, then placing it at a temperature of -25 to -15°C for 11 to 13 hours, and then freeze-drying it to obtain a PVA-CS-polyacid aerogel-modified carbon paper; (3) The PVA-CS-polyacid aerogel-modified carbon paper was placed in a N2 atmosphere and carbonized at 700-900°C for 2-4 hours. The carbonized material was then placed in a solution containing chloroplatinic acid for electrodeposition to obtain a polyacid-hydrogel-based self-supporting electrocatalyst.

2. The preparation method according to claim 1, characterized in that: In the step (1), a certain mass of CS is weighed and dissolved in a 1% glacial acetic acid solution, and stirred until dissolved to obtain a 2.5% CS solution; a certain mass of PVA is weighed and added to deionized water, and stirred at 80-95° C. for 1.5-2.5 hours to obtain a 10% PVA solution; the 2.5% CS solution and the 10% PVA solution are mixed at a CS:PVA mass ratio of 1:4, and stirred until uniform to obtain a PVA-CS solution.

3. The preparation method according to claim 1, characterized in that: In the step (2), the hydrophilic carbon paper is cut into 1×1.5 cm, immersed in the PVA-CS solution, and then scraped on both sides after immersion, and then placed in a 4% concentration borax solution for 30 seconds; The hydrophilic carbon paper may also be replaced by hydrophilic carbon cloth.

4. The preparation method according to claim 1, characterized in that: The ratio of the mass of the molybdate solution used in the step (2) to the mass of CS is (2-4):1, and the molybdate solution includes ammonium molybdate tetrahydrate.

5. The preparation method according to claim 1, characterized in that: In the solution containing chloroplatinic acid in step (3), the concentration of chloroplatinic acid is 20 μmol / L to 100 μmol / L.

6. The preparation method according to claim 1, characterized in that: In the step (3), the carbonized material is used as the working electrode, graphite is used as the counter electrode, and saturated calomel is used as the reference electrode, and electrodeposition is performed in a solution containing chloroplatinic acid. The deposition conditions are: in CV mode, the scan rate is 50 mV s -1 The deposition voltage range is 0 to -0.50 V versus RHE, and the cycle is 100 to 1000 cycles.

7. A polyacid-hydrogel-based self-supporting electrocatalyst obtained by the preparation method according to any one of claims 1 to 6.

8. Use of the polyacid-hydrogel-based self-supporting electrocatalyst as claimed in claim 7 in hydrogen production by water electrolysis.